Challenges to the Quality of Early Childhood Education Delivery at Pre-Primary Level at Five Schools in the Zambezi Region (Namibia) - Глорія Мубіана; Девід Нкенгбеза (Hryhorii Skovoroda University in Pereiaslav, 2023)
Objective. The primary purpose of this study was to document the nature of challenges faced by pre-primary teachers when delivering quality early childhood education at pre-primary schools in the Zambezi Region. The quality of delivery of early childhood education is crucial for the cognitive, emotional, physical and social wellbeing of children (Ministry of Education, Arts, and Culture [MEAC], 2016). The researcher envisaged that a high standard of delivery of early childhood education will potentially equip young children with skills and knowledge that will be important to their success during primary schooling. The study should prove essential for policy makers and other stakeholders to help them deliver early childhood education in pre-primary schools of a high standard in five schools that were purposefully selected for the study. Materials & Methods. The case study collected qualitative data using face-to-face interviews with pre-primary teachers and junior primary heads of department. Observations were conducted in pre-primary classrooms during the lessons. In addition, the documents were reviewed, which included ministerial documents, journals and newspaper articles, to gather data that could be used to facilitate the improvement of early childhood education in pre-primary schools. Results. The central question of study was: What are the challenges of quality delivery in early childhood education at the selected pre-primary schools? In order to answer this primary question, the following supporting questions were formulated: What are the challenges faced by pre-primary teachers in order to implement a curriculum that will provide quality early childhood education at the five schools in the Zambezi Region of Namibia? How does the classroom environment influence the delivery of quality early childhood education at the five selected pre-primary schools? Conclusions. The findings of the research revealed that several challenges inhibit the quality of delivery of early childhood education at the five pre-primary schools selected for the study in the Zambezi Region. These challenges included: the use of SiLozi as a medium of instruction, a discrepancy between learning objectives as presented in teacher's manual and in the curriculum, the lack of educational corners, the lack of teaching materials, the lack of recreational facilities and a deficiency in parental involvement in their children's schooling.